2018
DOI: 10.1002/cepa.868
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal assessment of internally insulated solid masonry walls fitted with exterior hydrophobization and deliberate thermal bridge

Abstract: Relative humidity (RH) and temperature were measured in several solid masonry walls with embedded wooden beams, fitted with autoclaved aerated concrete (AAC) thermal insulation on the interior surface and exposed to a cool, temperate climate. The field study was based on the use of a 40-feet insulated reefer container reconfigured with eight 1 × 2 m holes containing the solid masonry walls. The study investigated the influence of AAC thermal insulation on the interior side with a combination of exterior hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…This would mean less potential for diffusion in the outwards direction and in turn less interstitial condensation. Previous field studies [15], [37] and simulation studies [14], [15], [29], [31], [38]- [40] have shown improved hygrothermal performance in the critical locations in the case of reduced indoor moisture load. The case studies in [7], [21], [23], [24] showed acceptable performance in the interface between the existing wall and the insulation system while subjected to a low indoor moisture load (studies were primarily using diffusion-open systems).…”
Section: Introductionmentioning
confidence: 99%
“…This would mean less potential for diffusion in the outwards direction and in turn less interstitial condensation. Previous field studies [15], [37] and simulation studies [14], [15], [29], [31], [38]- [40] have shown improved hygrothermal performance in the critical locations in the case of reduced indoor moisture load. The case studies in [7], [21], [23], [24] showed acceptable performance in the interface between the existing wall and the insulation system while subjected to a low indoor moisture load (studies were primarily using diffusion-open systems).…”
Section: Introductionmentioning
confidence: 99%
“…Hourly data were used for the mathematical mould-growth modelling. Measurement data and VTT modelling results are available in the supplementary files [12]…”
Section: Resultsmentioning
confidence: 99%
“…This leads to reduced drying capability and perhaps increased moisture content in the wall when combined with covering the internal surface of the wall with a material. As a result, there is a possibility of moisture-related issues like frost damage at the exterior surface, rot in the wooden beam ends, high relative humidity, or even interstitial condensation at the interface of internal insulation and the original wall, where, as a result, mold may appear [2,[17][18][19].…”
Section: Internal Insulationmentioning
confidence: 99%